Kweekskool teenoor teologiese fakulteit: Die ervaring van die Nederduitse Gereformeerde Kerk - Brown, E. (Hervormde teologiese studies, 1994)
Seminary versus theological faculty: The experience of the Dutch Reformed Church This article poses the question of why the Theological Seminary initiated and established by the Dutch Reformed Church, became - after 104 years - the Faculty of Theology at the University of Stellenbosch. In a real sense it was a contextual and logical development. Right from the beginning, the church put a high value on a theological education connected to a university. However, considering the problems of faith and reason, church and culture, the Synod insisted on official guidance of the theological instruction of ministers in training. By agreement, the University adopted the Seminary as its faculty, allowing it to retain its name and identity. In this way the church obtained the required degree course for its students.